XAS studies of pressure-induced structural and electronic transformations in α-FeOOH. (29th May 2019) - Trcera, N; Layek, S; Shulman, M; Polian, A; Irifune, T; Itié, J-P; Rozenberg, G Kh
Abstract: Structural and electronic transformation taking place in α -FeOOH goethite have been studied by Fe K -edge x-ray absorption spectroscopy at pressures up to 50 GPa. These studies have shown the symmetrization of FeO6 octahedra coinciding with the Fe 3+ high to low spin transition at pressure above ~45 GPa. Our data are in excellent agreement with the results of recent single crystal XRD and Mössbauer spectroscopy studies (Xu et al 2013 Phys. Rev. Lett .111 175501), supporting the H-bonds symmetrization in iron oxyhydroxide, resulting from the Fe 3+ high-to-low spin crossover at above 45 GPa. Our study shows an applicability of the x-ray absorption spectroscopy in a further study of the H-bonds symmetrization phenomenon.